Comparison of mode-resolved fracture strength of silicon with mixed-mode failure of diamond crystals - Kozhushko, Victor; Hess, Peter (Engineering fracture mechanics, 2010)
Currently ab initio theory provides the ideal tensile and shear strength of the {111} cleavage plane in single-crystal silicon and diamond only for few selected planes and directions (‘geometries’). These values can be compared with the real strength of nano-, micro-, and single-crystalline devices to roughly judge their mechanical quality. A novel contact-free and notch-free optical laser method allows the measurement of the fracture strength with plane nonlinear surface acoustic waves (SAWs), providing a unique way to discriminate between tensile and shear stresses for well-defined crystallographic planes and directions in anisotropic materials. Calibration yields the critical fracture stress or strength for the geometries, which can be compared with theory. In the case of diamond mostly mechanistically unresolved mixed-mode failure has been studied for complex geometries. Nevertheless, the comparison of these critical failure stresses with the strength of the ideal lattice and the mode- and geometry-resolved fracture behavior of silicon provides new insight into the mechanical stability and failure behavior of diamond materials.